Effects of training with different hang-power-clean intensities on the maximum dynamic strength, vertical jump, and sprint performance of female handball players - Silva, C.; Berton, R.; Boccato, J.; Tricoli, V. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To compare the effects of 7 weeks of training with different hang-power-clean (HPC) intensities on the maximum dynamic strength, vertical jump, and sprint performance of female handball players.